2021
DOI: 10.1186/s12864-021-07719-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis reveals that EDNRB2 causes a dose-dependent loss of pigmentation in ducks

Abstract: Background Birds have various plumage color patterns, and spot is a common phenotype. Herein, we conducted genome-wide association studies (GWAS) in a population of 225 ducks with different sized black spots to reveal the genetic basis of this phenomenon. Results First, we quantified the black spot phenotype within the duck population. The results showed that the uncolored area of the body surface first appeared on the ventral side. With increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Thus, MC2R mediates ACTH to promote melanin deposition, which leads to the formation of grey feathers; however, the specific mechanism requires further experimental verification. Other studies have also reported that the EDNRB2 is a candidate gene associated with black color in live animals and poultry [ 55 , 56 ]. EDNRB2 is a key gene involved in melanogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MC2R mediates ACTH to promote melanin deposition, which leads to the formation of grey feathers; however, the specific mechanism requires further experimental verification. Other studies have also reported that the EDNRB2 is a candidate gene associated with black color in live animals and poultry [ 55 , 56 ]. EDNRB2 is a key gene involved in melanogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…EDNRB signaling is required for melanocyte development [ 61 , 62 ]. Loss of function variants in EDNRB leads to white spotting phenotypes in humans, animals [ 63 , 64 ], and poultry [ 65 , 66 ]. A similar result was identified in our study, which showed that EDNRB2 regulated melanin pigmentation in ducks.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the P -value and/or marker effect in GWAS, it is easy to obtain the SNP's effect on a phenotypic trait. At present, molecular markers associated with reproductive ( Chang et al, 2012 ; Huang et al, 2013 ), carcass ( Wu et al, 2012 ), body size ( Zhou et al, 2018 ), feather color ( Xi et al, 2021 ), and eggshell ( Liu et al, 2021 ) color traits have been discovered in ducks. However, less publications reported on ducks' QTLs or SNPs associated with feather growth traits.…”
Section: Introductionmentioning
confidence: 99%